2018
DOI: 10.4103/jfmpc.jfmpc_101_18
|View full text |Cite
|
Sign up to set email alerts
|

Associated head injuries and survival rate of patients with maxillofacial fractures in road traffic accident:A prospective study in Saudi Arabia

Abstract: Background:Every minute, an accident occurs in Saudi Arabia, causing 39,000 injuries and 7,000 deaths annually. Facial trauma or maxillofacial trauma (MFT) is a frequent presentation of road traffic accidents (RTAs), ranging from simple nasal fractures to gross or severe maxillofacial injuries.Methods:A total number of 237 patients were included in this prospective study from May 2013 to January 2018. The following medical details were recorded for each case, gender, age, fracture location, the presence of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Damage to the dental system due to injury in the car could occur when the person comes into contact with parts of the car, usually in frontal collisions, namely with the steering wheel, front panel, front windshield. This assumption of the mechanism of damage is consistent with the results of other similar studies [1,5,12,14,20,24,25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Damage to the dental system due to injury in the car could occur when the person comes into contact with parts of the car, usually in frontal collisions, namely with the steering wheel, front panel, front windshield. This assumption of the mechanism of damage is consistent with the results of other similar studies [1,5,12,14,20,24,25].…”
Section: Discussionsupporting
confidence: 92%
“…Of course, the most important objects of study in performing such examinations are the victims (corpses or living persons). In general, these issues have been carefully studied by both domestic [11,22,23] and foreign authors [1,10,17,18,19,24,25]. Particular attention in cases of accidents was paid to comprehensive studies [1,3,4,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Причинами травматизму є соціальна нестабільність, природні катаклізми, дорожньотранспорті пригоди, порушення правил охорони праці, збільшення випадків агресивної поведінки людей [7,8]. Варто зазначити, що в Україні збільшується число травм внаслідок дорожньотранспортних пригод на відміну від євопейських країн.…”
Section: стоматологіяunclassified
“…4,5,6 The WHO has documented that nearly one-third of traumatic injuries reported in developing countries are due to road traffic accidents (RTA) which significantly contribute towards increased mortality rates. 7,8 The purpose of the current study was to assess the association of age, gender, and mechanism of injuries in patients presenting at tertiary care facilities of Karachi, Pakistan. Locally reported data have shown that males are more prone to facial injuries during their 2nd and 3rd decades of life with the most common etiologic factor being road traffic accidents (RTA).…”
Section: Introductionmentioning
confidence: 99%